„Zaprawdę powiadam ci, poetą się jest…”. Wojaczek Lecha Majewskiego z 1999 roku - Grodź, Iwona (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
The theme of the text is the connection between the inspiration of the artists, for example poets, and their emotional states. The purpose of the text is to indicate the role of emotions in creative work. The subject of the analysis is the film Wojaczek made by Lech Majewski from 1999, about the young Polish poet – Rafał Wojaczek (1945-1971).